Does signaling work in markets for information services? An empirical investigation for insurance intermediaries in Germany - Martina Eckardt (Universität Rostock, Institut für Volkswirtschaftslehre, 2007)
Insurance intermediation services are information services which exhibit strong information asymmetries. We empirically analyze whether signaling works in the German market for insurance intermediation services. For this a signal must increase service quality and be easily identifiable by consumers so that it pays for intermediaries to spend the related costs. By using OLS and logit estimations we test whether intermediary type, reputational activities and a variety of signaling instruments work as credible signals. Our findings confirm the main hypotheses derived from signaling theory as to the poor working of market forces in markets for information services. Accordingly, public policy regulation is necessary to mitigate the resulting problems.
Keywords: D82; G22; L15; L86; 330; signaling; insurance intermediation; information services; Versicherungsvermittlung; Asymmetrische Information; Signalling; Dienstleistungsqualität; Theorie